PENGEMBANGAN SARANA USAHA SEBAGAI STRATEGI MENINGKATKAN DAYA TARIK DAN PENJUALAN PRODUK PIAARAS DI BUNUTWETAN MALANG - Indah Dwi Mumpuni; Dwi Safiroh Utsalina; Jauharul Maknunah (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
IRT PiaAras is a food-based microenterprise producing crispy pia cakes, located in Bunutwetan Village, Malang Regency. The business partner lacked adequate infrastructure to support product display and visual identity, and product sales remained suboptimal both offline and online. This community engagement program aimed to enhance PiaAras’ business capacity through the provision of business infrastructure, branding and social media training, and cost of production (HPP) calculation. The implementation included partner needs assessment, procurement of display showcase and neon signage, practical training using the HPPinAja application, and digital promotional content development supported by AI-based tools. The results showed significant improvements: 100% of business infrastructure was installed and utilized, 92% of HPP training participants were able to calculate selling prices independently, and 85% of promotional content was published through active social media accounts. The program produced tangible outputs including physical business assets, branding strategy training, digital promotional content, and HPP training, contributing to the strengthened capacity of PiaAras as a model for local microenterprise empowerment.